2019
DOI: 10.30848/pjb2019-6(38)
|View full text |Cite
|
Sign up to set email alerts
|

Leaf proteome analysis signified that photosynthesis and antioxidants are key indicators of salinity tolerance in canola (Brassica napus L.)

Abstract: Growth and yield reduction in different crops including canola is predicted to rise due to salinity stress in coming years. Understanding responses to salt stress will help in selecting and breeding salt tolerant canola cultivars. Physiological and leaf proteomic responses of 13 cultivars of canola were investigated under salt stress. In a pot experiment, three-week-old plants were grown under normal or salt stress (150 mM NaCl) for further two weeks. Out of 13 canola cultivars, cvs DGL, Dunkled, Faisal Canola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…After introgression of this trait, they developed salinity stress tolerant durum and bread wheat lines named Nax1 and Nax2 19 . It is important to mention here that genetic variation for salinity stress tolerance in a crop species cannot be explained due to one or two traits 2 , 20 , 21 . Plant’s ability to accumulate organic osmolytes such as soluble sugars and amino acids, activation of antioxidants to scavenge reactive oxygen species (ROS), down-regulating electron transport through photosystems to lower ROS generation are some important components of salt tolerance 1 10 , 20 , 22 .…”
Section: Introductionmentioning
confidence: 99%
“…After introgression of this trait, they developed salinity stress tolerant durum and bread wheat lines named Nax1 and Nax2 19 . It is important to mention here that genetic variation for salinity stress tolerance in a crop species cannot be explained due to one or two traits 2 , 20 , 21 . Plant’s ability to accumulate organic osmolytes such as soluble sugars and amino acids, activation of antioxidants to scavenge reactive oxygen species (ROS), down-regulating electron transport through photosystems to lower ROS generation are some important components of salt tolerance 1 10 , 20 , 22 .…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, physiological processes complemented with proteome profiling and/or transcriptome mapping in plants have gained popularity to explore mechanisms of salt tolerance [ 15 , 16 , 17 , 18 ]. Next-generation sequencing (NGS) has become a potential technique to evaluate molecular profiles for crop plants [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Carbon or carbohydrate metabolism occurs in the chloroplast, mitochondria, and cytosol of plant cells via the Calvin cycle, pentose phosphate pathway, glycolysis, and Krebs cycle (Barkla et al, 2013b;Taiz et al, 2015). Therefore, salt stress downregulates or upregulates several proteins associated with these metabolic pathways, as observed in rice (Nam et al, 2012;Liu et al, 2014), sorghum (Ngara et al, 2012), alfalfa (Xiong et al, 2017), canola (Iqbal et al, 2019), chickpea (Arefian et al, 2019) and Eutrema salsugineum (Goussi et al, 2021). Several studies have reported that salt stress reduces proteins related to chlorophyll biosynthesis, but increases thylakoidal proteins related to the light reaction (Barkla et al, 2013b; and references there in).…”
Section: Salt Stress Proteins Involved In Photosynthesis and Carbohyd...mentioning
confidence: 95%
“…Plants adapt to salinity stress by regulating the uptake and transport of Na + and K + ions, activating enzymes to scavenge reactive oxygen species (ROS), and improving osmotic adjustment (Kalaji and Pietkiewicz, 1993;Ashraf, 2009;Athar and Ashraf, 2009;Munns et al, 2020b). Proteins regulate these processes under normal and salt stress conditions (Li et al, 2017b;Li et al, 2017c;Iqbal et al, 2019), which are responsible for regulating cellular metabolism, organic and inorganic solute transport, water transport, osmoregulation, redox balance, sensing and signalling, hormonal balance, cell division, cell enlargement, and growth and development (Zhang et al, 2012a;Li et al, 2017c). In this review, we discussed the effect of salt stress on total soluble proteins, composition of proteins of different molecular weights, proteins related to various physiological and biochemical processes in halophytes and glycophytes or salt tolerant and salt sensitive cultivars of same species (Bose et al, 2017;Negrão et al, 2017;Pailles et al, 2020).…”
Section: Introductionmentioning
confidence: 99%